Antagonistic Effect of Coprophilous Fungi Against Colletotrichum sp. ST01 Causing Chili Anthracnose Disease - ขวัญมณี, สันทนา; พรหมพงษ์, สุทิน; เพิ่ม, อัจฉรา; ชอบบุญ, เสาวนิตย์ (KKU Science Journal, 2016)
Chili is one of an important economic crop of Thailand. Currently, chili is facing a problem of lower production caused by anthracnose disease from fungal pathogen, Colletotrichum spp. Most farmers use chemicals to control anthracnose in chili which directly affect environment and farmer’s health. The objective of this study was to evaluate for their antagonistic activities of coprophilous fungi against Colletotrichum sp. ST01 by dual culture technique on potato dextrose agar. Five of seventeen isolates (ST10, ST19, ST14, ST18, and ST16) showed high antagonistic activity of > 60% against Colletotrichum sp. ST01. The inhibition percentage of Trichoderma sp. TS10, Trichoderma sp. ST19, Aspergillus sp. ST14, Apergillus sp. ST18, and Ceratocystis sp. ST16 was 100.00±0.00, 100.00±0.00, 68.70±3.68, 67.87±2.38, and 63.70±3.60, respectively. Coprophilous fungi showed the potential to inhibit Colletotrichum sp. ST01 in laboratory level. It is possible that these fungi could be applied for controlling anthracnose disease in chili.